EFFICIENCY IMPROVEMENT OF FLAT PLATE SOLAR COLLECTOR USING SEARCH GROUP ALGORITHM - ABD RASHID, NURSABRINA (IRC, 2019)
Solar collectors are a widespread means of exploiting solar energy. They are special kinds of heat exchangers that transform solar radiation energy to internal energy of the transport medium. There are different kinds of solar collectors which can be distinguished by their concentration or not, the type of heat transfer liquid used, the temperature range of the working fluid, their and whether they are covered or uncovered. The evaluation of collector performance requires the calculation of the absorbed solar radiation and the heat loss to the surroundings. The equations describing these variables are developed in detail in this dissertation and they constitute the model for the collector numerical simulation. This document proposes new optimization technique, the Search Group Algorithm (SGA), to optimize the efficiency of flat plate solar collector.